Reproductive lifespan in association with risk of hypertension among Chinese postmenopausal women: Results from a large representative nationwide population - Hu, Zhen; Chen, Lu; Wang, Xin; Zhang, Linfeng; Chen, Zuo; Zheng, Congyi; Cao, Xue; Song, Yuxin; Zhou, Haoqi; Tian, Yixin; Cai, Jiayin; Huang, Yilin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between reproductive lifespan and risk of hypertension amongst postmenopausal women is unclear. Methods: A total of 94,141 postmenopausal women with a mean age of 64.8 years from the China Hypertension Survey were enrolled at baseline from 2012 to 2015. A standardized questionnaire was used to collect relevant information by well-trained interviewers. Blood pressure and physical examination of the participants was performed by trained medical staff. Logistic regression was used to estimate the odds ratios for hypertension by years of reproductive lifespan. Results: The average years of reproductive lifespan in Chinese women was 34.0 years. Women who were longer at reproductive lifespan were more likely to have older age at recruitment, higher body mass index, larger waist circumference, and have lower mean systolic blood pressure, and higher mean diastolic blood pressure (P<0.05). After adjustments, odds ratios (95% confidence interval) for hypertension were 1.035 (0.988-1.085), 1.007 (0.966-1.048), 1.000 (reference), 0.932 (0.899-0.967) and 0.953 (0.909-0.997) for those with reproductive lifespan at ≤28, 29-31, 32-34 (reference), 35-37, and ≥38 years, respectively. The significantly inverse association was seen in those with reproductive lifespan at 35-37 and ≥38 years. The overall risk of hypertension declined with the increase of reproductive lifespan, and the risk of hypertension reduced by 1.1% for every 1-year increase in reproductive lifespan (odds ratio, 0.989; 95% confidence interval, 0985–0.994) per year. The negative association between reproductive lifespan and hypertension was evident amongst age at recruitment groups, BMI categories, and education levels, with the strongest association amongst women aged ≥70years. Positive associations between reproductive lifespan and risk of hypertension were evident amongst women aged <60 years, and this association was stronger amongst current alcohol drinker. Conclusions: Based on the large nationally representative sample, Chinese postmenopausal women with shorter reproductive lifespan have higher risk of hypertension.